On regional variability of major soil microarthropod groups at four different edaphic systems in the northern alluvial plains of Bengal, India - Sarkar, S. K.; Chakrobarty, K.; Moitra, M. N. (Asian Journal of Biological and Life Sciences, 2015)
Soil samples were collected from four different sites - an agricultural field, a river basin, a brick field and a forest floor located in the alluvial plains of northern part of Bengal. Soil acarines dominated the region followed by collembolans. In a few collection efforts however, percentage abundances of collembolans appeared higher than acarines. Group-wise variation in microarthropod communities in the area was significant (p<0.05). Cluster analysis indicated greater similarity between agricultural field and forest floor than between brick field and river basin.
Keywords: Microarthropods; Percentage abundance; Similarity